Mobilites Contemporaines, Espace Et Liens Sociaux : Le Nomadisme Reinvente Et Ses Implications En Matiere De Planification Urbaine - Gazzeh, Karim (European Scientific Journal, ESJ, 2017)
Since the beginning of the 21st century, the modern society has witnessed an increased mobility as a vector for new lifestyles of the "civilization of mobility". Tied with the impressive developments in the information and communication technologies, the concept of mobility continues to be a significant challenge that needs to be considered while planning the city or studying the society. Comparing the contemporary society to the past nomadic communities appears as an approach that would explore and decrypt some socio-spatial phenomena where rapid transformations would be otherwise difficult to analyze using non-comparative methodologies. This article attempts to revisit some similarities between the contemporary society and the nomadic society in relation to the issue of mobility. The similarities are then analyzed with regard to two key concepts which shape the social pattern on the territories: the spatial reference and the nature of social links. The article ends with an exploration of proposals on how to take into account the contemporary mobility, henceforth smart, at the level of urban planning policies.